DOMINASI LAKI-LAKI TERHADAP PEREMPUAN BUGIS - Zainal Zainal (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This paper seeks to find the logic of marginalization of women in Bugis culture by shifting the orientation of the feminist movement which sees a great tendency to confront the